New visions in mathematics teacher education. a comparison of the recommendations and standars of professional nathematics societies and others interested in teacher preparation. Thomas G. Edwards y David R. Erickson - Erickson, David R
Compara las recomendaciones sugeridas por diversas organizaciones para cambiar la formación de maestros de matemática en los Estados Unidos